Character education and building the nation’s character through military conscription - Wakhudin (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to describe the role of military service in building the national character Indonesia needs today. This research employed a qualitative-descriptive approach, utilizing a discourse analysis method. The discourse analysis process was carried out by determining the text or discourse to be analyzed. In this case, the selected texts are "character education" and "military service." "Character education" was chosen because there is a suspicion that the decline of the Indonesian nation is caused by the continuing decline in the quality of its character. The research results indicated that military service is positively correlated with the health of the elderly, especially related to physical health, cognitive abilities, and self-assessment of health. Conscripts who participate based on self-awareness feel that military service is significant. There are several opposing opinions about military service, including the opinion that military service does not protect citizens who refuse it.